The Impact of Murrotal Al-Qur’an on Decreasing Labor Pain: A Systematic Review - Ika Sumiyarsi Sukamto; Siti Nurhidayati; Iffah Indri Kusmawati; Revi Gama Hatta Novika; Niken Bayu Argaheni; Mujahidatul Musfiroh; Erindra Budi Cahyanto; Luluk Fajria Maulida (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2021)
Background: Murottal Al-Qur'an therapy is a therapy for reading Al-Qur'an which is a religious therapy in which a person is recited verses from the Qur'an for a few minutes or hours so that it has a positive impact on one's body. Murottal Al-Qur'an recitation as a remedy for physical ailments.The aim of the study: To see the effect of murottal Al-Qur'an therapy on reducing the intensity of pain during labor.Method: Systematic review using the database: Google Scholar. The search results that meet the criteria are then analyzed the articles.Results: Pain in labor from many factors: 1) Anxiety and Stress, 2) Supporting Environment and Individuals, 3). Number of Deliveries and 4) Subjective Experience.Conclusion: There is an effect of offering murottal Al-Qur'an therapy on reducing pain intensity, where mothers who give birth after receiving Murottal Al-Qur'an therapy have a lower pain scale than mothers who give birth before getting Murottal Al-Qur'an therapy.Keywords: Murottal, Al-Qur’an, Labor Pain, Systematic Review